The Role of Agile Human Resources on Optimizing Gig Economy Mnagement in The Sharia Industry - Reni Febrina; Tartila Devi; Yenty Astarie Dewi; Habibatur Ridhah (Krisnadwipayana International Journal of Management Studies, 2026)
The rapidly growing gig economy phenomenon in the digital era has transformed work relationships into more flexible, project-based arrangements supported by digital platforms. However, this work model also presents challenges related to labour protection, welfare, and the fulfilment of workers' rights, especially in the context of the sharia industry, which demands human resource management in accordance with the principles of maqashid sharia. This research aims to analyse the role of Agile Human Resources (Agile HR) in optimizing gig workforce management in the sharia industry and to identify opportunities for its integration with Islamic values. The research uses a descriptive qualitative approach thru document analysis of various online secondary sources, including scientific publications, industry reports, and relevant company documents. The research results indicate that the application of Agile HR principles, such as work flexibility, cross-functional collaboration, adaptive decision-making, and performance-based evaluation, has begun to be adopted by several digital sharia companies to enhance the effectiveness of gig workforce management. Nevertheless, the implementation is still oriented toward operational efficiency and has not yet systematically integrated the principles of justice, protection of workers' rights, and welfare, which are the main objectives of maqashid sharia. This research emphasizes that Agile HR has the potential to become a strategic approach capable of bridging the need for business flexibility with the fulfilment of sharia values in gig workforce management. The research findings also point to the importance of developing an Agile HR framework based on maqashid sharia to create an adaptive, sustainable, and welfare-oriented human resource management system.